The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/jnci/dju091
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of Cancer Risk in BRCA1 and BRCA2 Mutation Carriers: A Systematic Review and Meta-Analysis

Abstract: Data assessing many potential risk modifiers are inadequate, and many have not been externally validated. Although additional studies are required to confirm some associations, sufficient information is available for some risk factors to be used in risk counseling or lifestyle modification to minimize cancer risk in BRCA1/2 mutation carriers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
142
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 71 publications
6
142
3
7
Order By: Relevance
“…However, although the prevalence of risk factors often differs across population subgroups, many breast cancer risk factors have been documented to operate across racial/ethnic groups, as would be expected from diseases with a common underlying biology (20,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Although we included family history as a nonmodifiable risk factor, we did not directly test for inherited mutations in genes that increase the risk of breast cancer; these are more common causes of breast cancer in younger, premenopausal women (53). This study also has a number of strengths.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the prevalence of risk factors often differs across population subgroups, many breast cancer risk factors have been documented to operate across racial/ethnic groups, as would be expected from diseases with a common underlying biology (20,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Although we included family history as a nonmodifiable risk factor, we did not directly test for inherited mutations in genes that increase the risk of breast cancer; these are more common causes of breast cancer in younger, premenopausal women (53). This study also has a number of strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have identified several other factors that can influence the risk of ovarian cancer such as parity, prior tubal ligation, salpingectomy and unilateral or bilateral oophorectomy (surgical removal of the ovary) (29,42,43). Women who have given birth have a reduced risk of all subtypes of ovarian cancer, with the strongest risk reduction noted for clear cell cancers, compared with women who have not given birth.…”
Section: [H2] Risk Factorsmentioning
confidence: 99%
“…(42). Tubal ligation and hysterectomy are also associated with a reduction in the risk of developing ovarian cancer; tubal ligation is associated with reduction in risk of clear cell and endometrioid carcinomas and hysterectomy is associated with reduction in risk of clear cell carcinoma (Wentzensen et al) (29,42,43).In one study, reproductive risk factors such as tubal ligation, parity of ≥2, endometriosis and younger age were more strongly associated with development of dominant ovarian tumors (meaning one ovarian tumour is at least twice as large as the tumour on the other ovary), than with non-dominant cancers which are thought to arise in the fallopian tube and are mostly HGSC (44). Also, endometriosis has been associated with endometrioid and clear cell ovarian cancer as well as low grade cancers (Wentzensen et al).…”
Section: [H2] Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations